Análisis de factores motivacionales en jóvenes de grado once de un colegio público en Bogotá para presentarse de forma voluntaria a prestar el servicio militar en el Ejército Nacional (2019)
The purpose of this research is to analyze the motivational factors in eleventh grade youth to voluntarily present themselves for military service in the National Army, personal, family, social and economic motivators are taken into account. It arises from the perspective of the armed conflict in Colombia and the controversy established against who are the young people who provide military service and what are their reasons, taking into account the abstention of young people to present themselves and the importance of the motivating factors in Decision making It is carried out from the phenomenological-hermeneutical approach, through a mixed research methodology of descriptive type, from which it was found that personal motivational factors predominate significantly, mainly the interest or taste for the military context, search for sensations and life project.